Political and Merchant Devotees: Multiple facets of pilgrimage to the medieval region of Braj (16th and 17th centuries) - Goel, Swati (The international journal of religious tourism and pilgrimage, 2016)
Braj is the epicentre of the Krishna cult. The physical representation of the scriptural Braj Mandala as we see it today, however, is a medieval construct. During the 15th and 16th centuries, as a part of religious exercises or in the quest for the land of Krishna, the propagators of various sampradayas (sects) reached the region seeking spiritual solace. This process of rediscovering Braj and the settlement of the various sects was followed by a thronging of the region by merchant-followers and, subsequently, by Rajput rulers from the adjoining kingdoms of Rajasthan and Bundelkhand. The pilgrimage to Braj created an environment conducive for traders, especially from Gujarat and Punjab, to establish economic links with the region through a process of endowment and exchange. Hundis (bills of exchange) and wealth in the form of jewelry and gifts from businessmen coming to Braj on a pilgrimage significantly contributed to the development of the region. Of note, however, pilgrimage undertaken by Rajput rajas (kings) was certainly an attempt to assert their authority and raise themselves in the hierarchy vis-à-vis other rulers and nobles. As Braj came to be associated with the Mughals, this pilgrimage also meant allegiance to the courtly culture. This paper establishes that the Braj pilgrimage has served multiple purposes other than quenching one's spiritual thirst. It served as a medium for legitimising the accumulation of wealth by merchants through their contribution to religious activities. It was also a platform for the formulation of community bonds where monetary help in adverse times could be sought, and safer business travel ensured. Unlike most medieval institutions, which have withered away with the passage of time, pilgrimage to Braj Mandala in the neighbourhood of Vrindavan and Gokul - comprising a circuit of 84 kos (around 252 kilometres) - is still a living tradition.